Whole genome sequencing reveals a de novo SHANK3 mutation in familial autism spectrum disorder. - Sergio I Nemirovsky; Marta Córdoba; Jonathan J Zaiat; Sabrina P Completa; Patricia A Vega; Dolores González-Morón; Nancy M Medina; Mónica Fabbro; Soledad Romero; Bianca Brun; Santiago Revale; María Florencia Ogara; et al. (PLoS ONE, 2015)
Introduction Clinical genomics promise to be especially suitable for the study of etiologically heterogeneous conditions such as Autism Spectrum Disorder (ASD). Here we present three siblings with ASD where we evaluated the usefulness of Whole Genome Sequencing (WGS) for the diagnostic approach to ASD. Methods We identified a family segregating ASD in three siblings with an unidentified cause. We performed WGS in the three probands and used a state-of-the-art comprehensive bioinformatic analysis pipeline and prioritized the identified variants located in genes likely to be related to ASD. We validated the finding by Sanger sequencing in the probands and their parents. Results Three male siblings presented a syndrome characterized by severe intellectual disability, absence of language, autism spectrum symptoms and epilepsy with negative family history for mental retardation, language disorders, ASD or other psychiatric disorders. We found germline mosaicism for a heterozygous deletion of a cytosine in the exon 21 of the SHANK3 gene, resulting in a missense sequence of 5 codons followed by a premature stop codon (NM_033517:c.3259_3259delC, p.Ser1088Profs*6). Conclusions We reported an infrequent form of familial ASD where WGS proved useful in the clinic. We identified a mutation in SHANK3 that underscores its relevance in Autism Spectrum Disorder.